Multiple introductions and human-aided dispersal of the UK’s most widespread non-native amphibian - Ball, Sarah E.; Gupta, Mollie; Aldridge, Sarah J.; Allen, Bryony E.; Faulkner, Sally C.; Oteo-García, Gonzalo; Griffiths, Richard A.; Hill, Peter; Morris, Nicola J.; Stevens, Michael C. A.; Wilkinson, John; Garner, Trenton W. J. (Frontiers in Amphibian and Reptile Science, 2023)
The alpine newt Ichthyosaura alpestris has achieved a widespread distribution as a non-native (alien) species in Britain since its initial introduction over a century ago, but the patterns of its release and subsequent dispersal have never yet been collectively analysed. We employed a multi-disciplinary combination of methods, using geographic profiling to estimate the likely number and locations of introductions, and mitochondrial DNA polymorphisms to investigate the likely geographic source of primary introductions, including the potential role of the pet trade. In parallel we used population genetic analysis and coalescence-based modelling to infer the demographics and directionality of dispersal from founding populations. Our results show that alpine newts have been released at multiple sites. We found a close resemblance between patterns of mtDNA haplotypes in the pet trade and those of established alpine newt populations, suggesting a relationship between trade, releases, and dispersal. Results from demographic modelling using Approximate Bayesian Computation are also consistent with multiple independent introductions with limited local dispersal, and additionally suggest that releases may occur from intermediate sources, such as captive populations. Our results support the hypothesis that deliberate human activity is largely responsible for both introductions of alpine newts into the UK and their wider dispersal post-introduction. The likely involvement of the international pet trade highlights the risk that ongoing releases of I. alpestris may expose native species to pathogens, whether pre-existing or novel.